ANALISIS KINERJA BADAN PERENCANAAN PEMBANGUNAN DAERAH (BAPPEDA) KABUPATEN SIDOARJO DALAM PENYUSUNAN RENCANA PEMBANGUNAN JANGKA MENENGAH DAERAH - Putri, Abigail Maharani; Bataha, Katerina (Jurnal Progress Administrasi Publik, 2024)
Development is a common issue faced by several regions in Indonesia. Regional development plans require the role of Bappeda in their implementation The importance of RPJMD in development planning is equally significant to the role and performance of Bappeda in formulating RPJMD for execution. The role of the Regional Development Planning Agency (BAPPEDA) is to serve as the starting point for determining the direction of development by maximizing resources and involving stakeholders in the development process. The purpose of this research is to determine the performance of the Sidoarjo District Development Planning Agency in formulating the 2021-2026 RPJMD The research was conducted using qualitative descriptive method, utilizing data from interviews, documentation, analysis, or observation. The data is then synthesized using a descriptive approach Descriptive methods analyze data in detail and provide a comprehensive and detailed overview of the phenomenon being studied. This research concludes that the performance of Bappeda Kabupaten Sidoarjo in formulating the RPJMD 2021-2026 meets five performance indicators: productivity, service quality, responsiveness, responsibility, and accountability. The performance indicator is in line with the results and processes of the preparation of the Sidoarjo Regency RPJMD for the period 2021-2025 carried out by several relevant government agencies together with the Sidoarjo Regency Bappeda.   Keywords: Bappeda; Performance; RPJMD